Pengaruh Ukuran Perusahaan, Leverage, dan Keputusan Investasi terhadap Nilai Perusahaan pada Perusahaan Pertambangan Sub Sektor Batubara yang Terdaftar di BEI Tahun 2016 – 2018 - Alqorina Wahyu Utami; Hari Nurweni (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
Abstract This study aims to determine the effect of Firm Size, Leverage, and Investment Decisions on Firm Value. The sample of this research is the coal sub-sector mining companies listed on the Indonesia Stock Exchange from 2016-2018. The sampling technique using a purposive sampling technique and obtained 14 companies, where the sample company has the criteria of having published the annual financial report for a specified period. The analytical method used is using the panel regression analysis method. The results of the data concluded that firm size has a negative and significant effect on firm value, leverage has a positive and significant effect on firm value and investment decisions have a positive and significant effect on firm value.Abstract This study aims to determine the effect of Firm Size, Leverage, and Investment Decisions on Firm Value. The sample of this research is the coal sub-sector mining companies listed on the Indonesia Stock Exchange from 2016-2018. The sampling technique using a purposive sampling technique and obtained 14 companies, where the sample company has the criteria of having published the annual financial report for a specified period. The analytical method used is using the panel regression analysis method. The results of the data concluded that firm size has a negative and significant effect on firm value, leverage has a positive and significant effect on firm value and investment decisions have a positive and significant effect on firm value.